2018
DOI: 10.1515/jpm-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

A soft cervix, categorized by shear-wave elastography, in women with short or with normal cervical length at 18–24 weeks is associated with a higher prevalence of spontaneous preterm delivery

Abstract: A soft cervix at 18-24 weeks of gestation increases the risk of sPTD <37 and <34 weeks of gestation independently of cervical length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 88 publications
8
58
0
3
Order By: Relevance
“…Subsequent studies; however, by Hernandez‐Andrade et al . and other authors demonstrated that when pregnancy progresses, cervix becomes shorter and softer; furthermore, a short cervix tends to be soft …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Subsequent studies; however, by Hernandez‐Andrade et al . and other authors demonstrated that when pregnancy progresses, cervix becomes shorter and softer; furthermore, a short cervix tends to be soft …”
Section: Discussionmentioning
confidence: 82%
“…We compared this study with two relevant studies, the first one by Muller et al . and the latter by Hernandez‐Andrade et al . In our study, the gestational age was limited to 18–24 weeks which is the time when cervical length measurement should be performed (similar to Hernandez‐Andrade et al .).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 11 clinical studies in the last three years, which tested the hypothesis that cervical elastography may be useful in predicting preterm delivery [20]- [25] [34] [35] [36] [37] [38]. Of the eleven studies identified, seven used strain ultrasound [20]- [25] [35] and four used shear wave ultrasound [34] [36] [37] [38]. These studies assessed between 30 and 628 subjects with a total of 1901 women in the eleven studies.…”
Section: Discussionmentioning
confidence: 99%
“…Strain ultrasound elastography determines only the relative values of tissue elasticity because the applied transducer pressure is unknown. The shear wave ultrasound elastography provides, in principle at least, a more objective description of tissue elasticity; however, the cervical elasticity is described as a shear wave speed [34] [36] [37] [38], but not as Young's modulus which requires solution of the inverse mechanical problem in absence of stress data. There are several difficulties in using this approach: 1) cervical tissue heterogeneity implies distortions in the shear wave elasticity estimates, 2) placing a transducer next to the cervix is likely to cause a tissue deformation, thereby causing a non-controllable increase in the tissue stiffening, 3) any movement should be avoided for 3 -5 seconds with a shear wave transducer, and 4) it requires a special transducer [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation